KEARIPAN LOKAL TANAMAN OBAT MASYARAKAT DAYAK AGABAG DI KABUPATEN NUNUKAN KALIMANTAN TIMUR - Nurul Puspita Palupi (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2013)
Indonesia is a country with the second largest palnt biodiversity in the world, where in the biodiversity, the potential stored medicinal palnts that have not been explored to the maximum. The potential is very large to ensure the health and welfare of the people if well utilized. In addition to the wealth of plant diversity, Indonesia is also rich in ethnic and cultural diversity. Central Bereau of Statistics (BPS) said in Indonesiahas 1,128 tribes scattered across the country. Each tribe has a different repertoire, and at any rate, there is a wealth of diverse indigenous communities, including the use of herbs for traditional medicine.It needs to be done in connection with exploration and inventory of medicinal palnts and their utilization in the community based on local wisdom. Research to obtain data fitogeografi, agro-climate, utilization based on local wisdom, phytochemicals, and socio-economic of medicinal plants will be very important in building a database that can be used as an important information in the process of domestication of medicinal plants to increase productivity in terms of both quality and quantity, as well as pilot plant based drugs for independence. Thus, the saintifikasi herbs can be developed at the same time throughout the health care facility.East Kalimantan is one of the provinces that have the richness and diversity of plants, as well as ethnic/tribes spread over 13 districts. One of the tribes that Agabag Dayak Tribe, who live and occupy the area and surrounding counties Nunukan.This research was conducted with the Snowball Sampling especially in determining the informant/battara. How to do the sanpling informant seeking information from the public and based on the testimony of indigenous community leaders, chiefs, village heads, headmen, and other reputable sources in the community (road user) the informant/Battara determined. In this study the informants gained 5/Battara from 4 villages (upper cape, lower cape (intin), banyan and Kalampising.